L’École de Bologne passée au crible - Francesca Lui (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
By 1796, Bologna, the second capital of the Papal State, was unsettled by the events of the Napoleonic occupation, which had many implications for the impressive artistic heritage of the town. Several archival records document the measures taken in the city to protect and restore its precious heritage by the Accademia Clementina, appointed to watch over it.